Examining the impact mechanism of intra-team co-opetition on employee creative deviance - Zhang, Min; Zhang, Jinyu; Lin, Qingxuan; Wang, Lei; Zhang, Xufan; He, Siyu; Nie, Zitong (Frontiers in Organizational Psychology, 2025)
BackgroundCreative deviance is key to producing breakthrough innovations and maintaining core competencies for a team. In contrast, intra-team co-opetition, an important influence on the allocation of team resources, may affect employees' creative deviance.MethodsThis study analyzed the impact mechanism of intra-team co-opetition on employee creative deviance based on the conservation of resources theory. We collected data from 205 employees in scenario experiment and 354 employees in the questionnaire.ResultsThe findings of polynomial regression and response surface analysis indicate that consistency in competition and cooperation within teams can lead to lesser knowledge power loss. When competition and cooperation levels within teams are inconsistent, they may not be able to attain their intended results. Furthermore, we found that when competition and cooperation levels within teams are inconsistent, knowledge power loss in the “low competition-high cooperation” combination was lower than the “high competition-low cooperation” combination. Thus, knowledge power loss can mediate between intra-team co-opetition and employee creative deviance.ConclusionThis study reveals the micro-mechanism of different combinations of co-opetition within the team, enriches the research results in the field of co-opetition and creative deviance, and provides reference for promoting team innovation performance and emerging more breakthrough innovation achievements.